Strategi Pemasaran Untuk Meningkatkan Kemampuan Bersaing Pada Spartyshop Bali - Duwitayanti, NI Made Nita; Adi, Ida Ayu Sri Puspa; Iswarini, Ni Ketut (Journal of Hospitality Accommodation Management (JHAM), 2024)
Spartyshop is a flower business in the Denpasar area that was founded in 2015. The large number of businesses that offer products and services similar to Spartyshop can be a threat to the development of their business. So a strategy is needed to maintain and develop the business, especially in social media. The purpose of this research is to find out the strategies that Spartyshop can use to maintain and develop its business through social media. So that it can be used as a reference by Spartyshop as a strategy for maintaining and developing business through social media. The research method used is interviews and documentation, then the data obtained can be analyzed using qualitative descriptive methods. Based on the SWOT analysis technique by combining internal factors such as strengths and weaknesses, and external factors such as opportunities and threats from the Spartyshop business. This analysis produces several strategies that can be carried out by Spartyshop, such as: maximizing social media reach to promote products, collaborating with influencers, creating interesting content, and improving the online shopping experience that supports delivery services. Promotion strategies via social media will continue to be carried out by Spartyshop Bali to maintain and increase sales.